If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(6x-5)+4(11-5x)=5(3x+5)-2
We move all terms to the left:
6(6x-5)+4(11-5x)-(5(3x+5)-2)=0
We add all the numbers together, and all the variables
6(6x-5)+4(-5x+11)-(5(3x+5)-2)=0
We multiply parentheses
36x-20x-(5(3x+5)-2)-30+44=0
We calculate terms in parentheses: -(5(3x+5)-2), so:We add all the numbers together, and all the variables
5(3x+5)-2
We multiply parentheses
15x+25-2
We add all the numbers together, and all the variables
15x+23
Back to the equation:
-(15x+23)
16x-(15x+23)+14=0
We get rid of parentheses
16x-15x-23+14=0
We add all the numbers together, and all the variables
x-9=0
We move all terms containing x to the left, all other terms to the right
x=9
| -3(5p+3)-2(5-17p)=3(2+6p) | | 8x/5=2 | | 7x+10-x=7+5x-10 | | -2(x-1)-5(2x+1)+4(2x-7)=0 | | 15-x-2=35 | | 6-7x=-69 | | 7x+9=13x+11 | | a/4-6=-4 | | (2x-9)=(37-4x) | | 1-b=0 | | 5/5x+7=1/8x | | -4-w=-8 | | 1-3x=7-2(1-x) | | -7=0-m | | 2y-(1-5y)-21=0 | | 0=o+-8 | | Y=4•+x | | 2y-(1-5y)-21=20 | | 12•=7y-10y | | |3x+4|=1 | | 4^x=12 | | x²+24x-20x-480=0 | | 2D^2+7d+3=0 | | 1-2(1-3(x-4))=9x+4 | | 4(x+50)=2x+18 | | 4^18-1=687194a6573 | | -2/5c-8=33 | | (6x-1)(x+2)=(3x+4)(2x+5) | | -7(a+1)-9(a+4)=0 | | 5(x-1)+7(x+4)=0 | | Y=4+3x-^2 | | 7z+2z=8z+5 |